Aryl hydrocarbon receptor and IL-13 signaling crosstalk in human keratinocytes and atopic dermatitis - Proper, Steven P.; Dwyer, Alexander T.; Appiagyei, Andrews; Felton, Jennifer M.; Ben-Baruch Morgenstern, Netali; Marlman, Justin M.; Kotliar, Michael; Barski, Artem; Troutman, Ty D.; Rothenberg, Marc E.; Mersha, Tesfaye B.; Azouz, Nurit P. (Frontiers in Allergy, 2024)
AD atopic dermatitis AHR aryl hydrocarbon receptor DEG differentially expressed gene DMSO dimethylsulfoxide EGFR epidermal growth factor receptor FICZ 6-formyl-indolo[3,2-b]carbazole H3K27ac histone 3 lysine 27 acetylation IL interleukin KC keratinocyte NRF2 nuclear factor erythroid 2-related factor 2 PCA principal component analysis PCB polychlorinated biphenyl PPI proton pump inhibitor scRNAseq single-cell RNA sequencing STAT6 signal transducer and activator of transcription 6 TCDD 2,3,7,8-tetrachlorodibenzo-p-dioxin Th2 T helper type 2